Use of information technologies in teaching course "Analytical geometry" in higher schools on example of software "ANALYTICAL GEOMETRY" - GrigorievaV.B. (Journal of Information Technologies in Education (ITE), 2009)
In article are considered the methodical questions of using of computer technologies, for example, the software "Analytical geometry", in process of teaching course of analytical geometry in the higher school.